Effect of endophytic entomopathogenic fungi on soybean Glycine max (L.) Merr. growth and yield - Russo, M. L. (2018)
The soybean is a crop of economic importance and has a great number of potential pests which cause significant economic losses. The entomopathogenic fungi Beauveria bassiana, Metarhizium anisopliae and Metarhizium robertsii are important biological control agents, which can live as endophytes within plants and causes no apparent damage to the host. The aims of this study were to assess whether the entomopathogenic fungi B. bassiana, M. manisopliae and M. robertsii are able to colonize soybean plants as endophytes by using different inoculation techniques; and assess if these fungi produce any effect on the growth and yield of soybean plants under field conditions. We demonstrate the effectiveness of three inoculation methods (foliar spray, seed immersion and root immersion) to establish fungal entomopathogens as endophytes. Percentage of recovery for the different fungal strains was higher after 7 days of inoculation, through the organ that was in direct contact with the fungus during the inoculation. B. bassiana LPSc 1098 inoculated by leaf aspersion was the most successful strain. It was also demonstrated for the first time that inoculation with B. bassiana promoted the growth and increased the yield of soybean plants under filed conditions, with no adverse effects observed in the inoculated plants.